COMPARATIVE ELECTRON-MICROSCOPIC AND MICROBIOLOGICAL INVESTIGATION OF SILVER PROTEINATE PREPARATIONS - V. A. Burmistrov; V. I. Zaykovskiy; A. V. Burmistrov; L. N. Rachkovskaya; A. V. Shurlygina; T. V. Popova; M. V. Robinson; M. A. Korolev; A. Y. Letyagin (Сибирский научный медицинский журнал, 2019)
The purpose of this work was a comparative study of the particle sizes of commercial preparations of colloidal silver by the method of electron microscopy, in connection with the characteristics of specific antimicrobial activity of the preparations under the same conditions. Four commercial preparations of colloidal silver were investigated: Vitargol Forte (manufactured by NPC «Elusan»), Protalor (manufactured by OOO «Esko-Farm», Armenia), Sialor (manufactured by PFK «Obnovlenie»). Protargol (prescription drugstore) served as the drug of comparison. Material and methods. The silver particle sizes in the preparations were determined by high-resolution transmission electron microscopy using a JEM 2010 electron microscope (JEOL, Japan) with a resolution of 0.14 nm at an accelerating voltage of 200 kV. The antimicrobial activity of the silver protein preparations was studied by a standard serial dilution method in liquid nutrient media and diffusion method using bacterial cultures of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Results and discussion. Vitargol Forte, manufactured using advanced technology, is the most fine-dispersed and monodisperse preparation. The preparation of standard classical Protargol, prepared in pharmacy conditions, was the most coarsely dispersed and polydispersed. The conclusion. The dependence of antimicrobial activity of the preparation on the size of its silver particles was shown. Of the four investigated preparations of silver proteinate, the smallest particle size was in the Vitargol Fort preparation. The same drug showed the highest bactericidal and bacteriostatic activity.